Contrôle moteur lombo-pelvien de joueurs de tennis élites avec et sans antécédent de lombalgie - Grosdent, S.; Colman, D.; Demoulin, C.; Kaux, J. F.; Roussel, N.; Vanderthommen, M. (Science & Sports, 2023)
Objectives The purpose of this cross-sectional study is to investigate the prevalence of impaired lumbopelvic motor control in elite tennis players with disabling episode of low back pain in the previous year.